Material conneXion materialenboek : internationale collectie van nieuwe en innovatieve materialen voor architecten, ontwerpers en kunstenaars. - Beylerian, George M., ....-; Dent, Andrew, ....- (Amsterdam : Bis, 2005)
The book comprises seven main sections-metal; glass; ceramics; polymers; natural and naturally derived materials; carbon-based materials; and cement-based materials - in which the authors define substances according to their base compositions rather than their current uses, which enables the reader to gain a clearer understanding of each material's potential and applications. Leading international designers, architects and artists reflect on the vital role of materials in modern design, while dazzling colour illustrations of actual designs and products and a detailed reference section encourage further ideas. The 'X' in ConneXion is the perfect symbolic crossroads: this is a book that connects material to designer, for whom Material ConneXion will be essential reading.
Vertaald uit het Engels.
Keywords: Materialen